2021
DOI: 10.21203/rs.3.rs-137764/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome Analysis of Ovary Tissues From Low- and High-yielding Changshun Green-shell Laying Hens

Abstract: Background: Changshun green-shell laying hens are unique to Guizhou Province, China, with high egg quality. At this stage, improving egg production performance has become an important breeding task. In recent years, the development of high-throughput sequencing technology provides a fast and exact method for genetic selection. Therefore, this study is based on high-throughput sequencing technology to analyze the differences in the ovarian mRNA transcriptome of low-yield and high-yield Changshun green-shell lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…Our results suggest that these pathways have been enriched, indicating their functions in the regulation of chicken egg production. However, our results are not consistent with those of Zhang et al (2019) and Mu et al (2021), who also conducted an RNA-seq analysis in chicken ovaries. Zhang et al (2019) identified four known pathways related to reproduction.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results suggest that these pathways have been enriched, indicating their functions in the regulation of chicken egg production. However, our results are not consistent with those of Zhang et al (2019) and Mu et al (2021), who also conducted an RNA-seq analysis in chicken ovaries. Zhang et al (2019) identified four known pathways related to reproduction.…”
Section: Discussioncontrasting
confidence: 99%
“…Among them, the focal adhesion and cytokine-cytokine receptor interaction pathways alone showed similarities with our results. Although Mu et al (2021) reported nine pathways, no pathways overlapped with our results. These conflicting results may be attributed to the differences in the chicken breed used in the respective experiments.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…GnRH signaling is regarded as the gonadotrope and endocrine control of fertility in mice (61) and goose (62). In chicken, GnRH signaling pathway could involve in ovarian function (49,63). Here, the nonadditive genes, such as MMP2, ADCY6, EGR1, CACNA1C and GNAQ, were identified significantly enriched in GnRH signaling pathway.…”
Section: Discussionmentioning
confidence: 87%